Chapter 12 — Developing a Preventative Pruning Program: Young Trees - Edward F. Gilman; Amanda Bisson (EDIS)
ENH-1062, an 11-page full-color fact sheet by Edward F. Gilman and Amanda Bisson, is part of the Urban Forest Hurricane Recovery Program series. It describes the components of preventive structural pruning, discusses how to determine pruning objectives, the pruning cycle and, proposes how to implement a preventative pruning plan for young trees in your community. Published by the UF Department of Environmental Horticulture, September 2007.